2013
DOI: 10.2174/1874434601307010096
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perceived Barriers to and Facilitators of Research Utilization in Mainland China: A Cross-Sectional Survey

Abstract: Despite the drive towards evidence-based practice, the extent to which research evidence is being implemented in nursing practice is unclear, particularly in developing countries. This study was to assess the levels of perceived barriers to and facilitators of research utilization in practice among Chinese nurses and inter-relationships between these barriers and facilitators and their socio-demographic characteristics. A cross-sectional, descriptive survey was conducted in 2011 with 743 registered nurses rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 38 publications
(94 reference statements)
11
47
0
5
Order By: Relevance
“…Meanwhile, constructivist grounded theory also emphasising on revealing patterns and connections rather than to linear reasoning and emphasises understanding rather than explanation (Charmaz, ). In this study, we found the factors ranging from the evidence level, nurses level, patient level, system level and outside system level, which were generally consistent with the literature from other countries (Ploeg, Davies, Edwards, Gifford, & Miller, ; Solomons & Spross, ; Yagasaki & Komatsu, ), as well as the previous published Chinese surveys (Chien et al., ; Wang et al., ; Zhou et al., ). However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence‐based nursing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, constructivist grounded theory also emphasising on revealing patterns and connections rather than to linear reasoning and emphasises understanding rather than explanation (Charmaz, ). In this study, we found the factors ranging from the evidence level, nurses level, patient level, system level and outside system level, which were generally consistent with the literature from other countries (Ploeg, Davies, Edwards, Gifford, & Miller, ; Solomons & Spross, ; Yagasaki & Komatsu, ), as well as the previous published Chinese surveys (Chien et al., ; Wang et al., ; Zhou et al., ). However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence‐based nursing.…”
Section: Discussionsupporting
confidence: 91%
“…In Chien et al. ()'s study, six of the top 10‐ranking barriers listed by 743 registered nurses from four general hospitals came from the subscale “organisational characteristics.” And these barriers were associated with a few socio‐demographic factors (age, education, postregistration experience and research training undertaken). Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies revealed different barriers proposing the problem as a multi‐faceted issue. The most cited barrier that almost 86% of the reviewed studies have addressed included lack of enough time to perform a search …”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study showed that not having enough time to conduct a search was a major barrier noted by almost 81% (n = 17) of the reviewed studies. 4,20,27,[35][36][37][38][39][40][41][42][43][44][45][46][47][48] Jones et al interviewed clinical nurses and in his paper argued that nurses do not have the required time to perform a search for patients' educational needs especially if the patients are waiting and the search takes too long, it will be abandoned. 35 Others mainly focused on the limited time nurses have at work to search and read evidence based content.…”
Section: Time Requirementsmentioning
confidence: 99%
“…Other identified barriers in the literature include: (a) lack of confidence in their ability to participate in a research study, (b) lack of understanding of nursing research design and methods, (c) perceived role conflict as both a researcher and clinical nurse, (d) challenges of gaining the cooperation of clinical nursing staff to comply with clinical trial protocols, (e) difficulties in maintaining clinical research team motivation, (f) lack of relevant, clinically focused research findings to implement (i.e., results are viewed as not useful for their practice), and (g) limited mentorship opportunities with a nurse scientist who has release time from other academic responsibilities. 8,12,14,15,16 …”
Section: Introductionmentioning
confidence: 99%